Unveiling the emotional labor of overseas Filipino international teachers - Baylosis, Leomar O.; Amante, Ivy F.; Banguis, Rovy M.; Genovia, Aldin Paul S.; Cedeño, Shem A. (International Journal of Evaluation and Research in Education (IJERE), 2025)
Emotional labor at work typically manifests through surface acting and deep acting. This phenomenological study examines the emotional labor experienced by 15 international Filipino teachers working in the United States, Saudi Arabia, and Thailand. Guided by self-determination theory (SDT), the research explores their reasons for teaching abroad, as well as the challenges they face and how they navigate them emotionally. A qualitative design was employed using semi-structured interviews and framed narratives. Each participant engaged in one individual interview and one focus group discussion. Data were analyzed using interpretative phenomenological analysis (IPA) to generate key themes. Findings show that deep acting involves emotional control, display of positive emotions, emotional exhaustion, experience of negative emotions, and emotional indifference toward self. In contrast, surface acting includes masking emotions, projecting artificial feelings, and withdrawal behaviors. The five major themes emerged as contributing factors to emotional labor: cultural adjustment, language barrier, professional challenges, limited support networks, and work-life balance. Coping strategies identified include emotional regulation, positive cognitive response, support from family and peers, and participation in recreational activities. These nuanced findings offer important insights for international teacher preparation, emotional well-being, and future research on cross-cultural educational contexts.